Peningkatan Daya Tarik Wisata melalui Pembuatan Video Promosi Geosite di Desa Jari Kecamatan Gondang Kabupaten Bojonegoro - Indriani, Yulia; Saputra, Dani Adi; Tunggal Dewi, Tahta Tribuana; Bilqinaristi, Chairissa; Pratama, Irfan Adi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Jari Village, located in Gondang Subdistrict, Bojonegoro Regency, possesses significant geotourism potential through the presence of the Selo Gajah and Banyu Wedang Geosites. However, this potential has not yet been fully optimized. The Thematic Collaborative Community Service Program (KKN-TK) Group 06 of Bojonegoro University was conducted with the aim of enhancing tourism appeal through the creation of an informative and educational promotional video. The video production process consisted of three main stages-pre-production, production, and post-production-which included idea planning, filming, and final editing. The result was a two-minute video showcasing the natural beauty, geological uniqueness, and educational value of the geosites. The distribution strategy utilized social media platforms such as Instagram, YouTube, and TikTok, along with collaborations with various stakeholders to expand promotional reach. This initiative proved effective in increasing the visibility of Jari Village as a geotourism destination while supporting efforts in geosite conservation and sustainable management.